Industry Payments to Orthopedic Spine Surgeons Reported by the Open Payments Database: 2014–2017. Issue 10 (December 2020) - Pathak, Neil; Mercier, Michael R.; Galivanche, Anoop R.; Mets, Elbert J.; Bovonratwet, Patawut; Bagi, Paul S.; Varthi, Arya G.; Grauer, Jonathan N.
Abstract : Study Design: This was a retrospective study of publicly available data. Objective: The objective of this study was to characterize and assess trends in Open Payments Database (OPD) industry payments reported to orthopedic spine surgeons from 2014 to 2017. Summary of Background Data: There have been a lack of studies characterizing OPD industry payments to orthopedic spine surgeons over the 4 full years of data available. Materials and Methods: General industry payments made to orthopedic spine surgeons from 2014 to 2017 were characterized by year with analysis of: number of compensated surgeons, median payment per surgeon, top strata of compensated surgeons, and subtype (ie, food/beverage). Research and Ownership Payments were characterized by median payment per surgeon. Mann-Whitney U tests were used to compare payments. Results: For General Payments, the number of compensated orthopedic spine surgeons increased from 1539 in 2014 to 1673 in 2017. Later year median General Payments per surgeon were compared with the 2014 median (1051): 2015 (1070: P =0.375), 2016 (1263: P =0.012), and 2017 (978: P =0.561). In 2014, the top 10% of compensated orthopedic spine surgeons received 89% of the total General compensation to orthopedic spine surgeons, top 5% received 79%, and the top 1% received 55%. The median General Payment for these 3 top strata remained similar over the 4 years evaluated ( P >0.05). For subtype analyses, the median aggregate General Payment for "education" increased ( P =0.002) across the years. Finally, it was determined that the median payment per surgeon for Research and Ownership Payment categories remained stable across the time period ( P >0.05). Conclusions: Many expected industry payments to surgeons to decrease under public scrutiny of the OPD, but the present study showed no net change in median payment (General, Research, and Ownership) over the years studied. In the age of greater transparency, these findings shed insight into the orthopedic spine surgeon-industry relationship. Level of Evidence: Level III.